Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2174/1385272824999200709125407
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Ring-opening Polymerization of ε-caprolactone Initiated by Degradable Biopolymers

Abstract: : The article reviews the research progress in the preparation of polycaprolactone through the ring-opening polymerization of -caprolactone initiated by biopolymers in recent years. The structure characteristics of starch, cellulose, chitosan, polyhydroxyalkanoates, polylactic acid, the reaction mechanism, the preparation method and the application of - caprolactone were introduced. Finally, the future development of new polycaprolactone copolymers is prospected. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Organocatalysts, which have been extensively surveyed since the pioneering work of Hedrick and Waymouth over the last two decades, have also been used prominently to proceed the ROP of TMC, and they typically include organic acids (e.g., sulfonic and phosphoric acids and their derivatives) and organic bases (e.g., guanidine, amidine, and carbene) [ 21 , 22 , 23 , 24 , 25 ]. Aiming at how acidity affected catalytic activity, Hedrick and co-workers used molecular modeling to calculate the energy based on the reaction mechanism, and the results showed that catalysis is indeed dependent on both acid strength and the ability of the conjugate base to act as a hydrogen-bond acceptor, suggesting the superiority of bifunctional activation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organocatalysts, which have been extensively surveyed since the pioneering work of Hedrick and Waymouth over the last two decades, have also been used prominently to proceed the ROP of TMC, and they typically include organic acids (e.g., sulfonic and phosphoric acids and their derivatives) and organic bases (e.g., guanidine, amidine, and carbene) [ 21 , 22 , 23 , 24 , 25 ]. Aiming at how acidity affected catalytic activity, Hedrick and co-workers used molecular modeling to calculate the energy based on the reaction mechanism, and the results showed that catalysis is indeed dependent on both acid strength and the ability of the conjugate base to act as a hydrogen-bond acceptor, suggesting the superiority of bifunctional activation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most commercialized PCL synthesis, ring-opening polymerization (ROP) is the preferable route ( Li et al, 2020 ; Rosa et al, 2021 ). This process is a one-step polymerization that can be catalysed by various metal complexes ranging from simple metal halides to complex organometallics ( Kundys et al, 2018 ; De Hoe et al, 2022 ), and can be controlled in terms of the molecular weight (Mwt) and the polydispersity (Ð).…”
Section: Introductionmentioning
confidence: 99%